The feasibility of direct adductor canal block (DACB) as a part of periarticular injection in total knee arthroplasty - Bagaria, Vaibhav (Knee Surg Relat Res, 2020)
BACKGROUND: Adductor canal block (ACB) is one of the preferred methods of analgesia in total knee arthroplasty (TKA). However, conventionally its use is time-consuming, requires ultrasound guidance, a trained anaesthesia team and adherence to strict asepsis by members of the allied teams. This study was done to assess the feasibility and safety of direct adductor canal block (DACB) as a part of surgeon-administered periarticular infiltration. MATERIALS AND METHODS: Thirty computed tomography (CT) angiography films of the patients were retrospectively reviewed. The trajectory of the needle placement for a DACB in relation to the target region of the adductor block was determined. Fourteen knees in seven cadavers, were dissected through a medial parapatellar approach to perform TKA. After administering the DACB using the technique based on CT data, dissection was carried out to ascertain the correct placement of the dye by visualising the stained areas. RESULTS: The angle of approach in the coronal plane from the entry point to the medial high point and to the adductor hiatus was 10.2° (8−14°) and 6° (3.8−11°), respectively. The angle of approach in the sagittal plane from the entry point to the medial high point and to the adductor hiatus was 7° (5−10.5°) and 29° (19−43°), respectively. In all the 14 cadaveric knees, we confirmed the correct placement of the methylene blue dye as demonstrated by the staining of the adductor canal. CONCLUSION: The study demonstrates the feasibility of the DACB. This surgeon-driven technique is likely to reduce the cost of the procedure, reduce operating room time and also eliminate the risks of surgical-site contamination.